Study of the Message of Feminism and Post-Colonialism in Babad Diponegoro Painting Pupuh Sinom XIV by Isur Suroso - BAYU SETIAWAN (LPPMPP Institut Seni Indonesia Padangpanjang, 2020)
In the painting about Babad Diponegoro entitled “The Garden Of Earthly Prosperity In Ground Zero” by Isur Suroso, contain meaningful messages. Every sign in the painting contain messages that represent different meaning. A lot of signs in the painting visualized feminism and pos-tcolonialism.. There are many contradictive but interrelated between signs. There are abundant messages about colonialism time in 19 century. The representation of the Prince Diponegoro, Prince’s grandmother, and abdi dalem are deformed to emphasize the message about post- colonialism and feminism. The message about feminism in this painting represented by showing women domination among men